ANALISIS PENENTUAN HARGA POKOK PENJUALAN DENGAN MENGGUNAKAN METODE FULL COSTING PADA PABRIK ROTI PELANGI NUSANTARA DI KOTA METRO - Aprilida Tia Soraya; Nani Septiana (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
For a company in the field of calculating the pricing of the essentials, it is the right and rational thing. This pricing is done with the primary goal for optimal profit. The purpose of this research is to use the full costing method at Roti Pelangi Nusantara Kota Metro Factory.The method used in this research is explanatory survey method. This research type is quantitative research with method of full cost price. Data collection using interviews, and documentation. The analytical tool used is a full cost measurement method.The resulted of the analysis of 25% accurate price obtained cost for full costing method of Rp. 7,250 per pack for the company method of Rp 7,100, the difference between the full costing price with the company method Rp. 150 per pack.Keywords: cost of production method of full costing